Plan de seguimiento y monitoreo para la población beneficiaria del Crédito de Desarrollo Humano Asociativo en organizaciones sociales del Cantón Babahoyo - Camejo Cortez, Melida Viviana (2014)
The tracking and monitoring plans are of great importance in entrepreneurial projects through the plan because it can assess the situation, social, economic and financial companies are these large, medium or small. The objective pursued is to determine the shortcoming of the course of social projects or investment be they public or private, through a monitoring plan and monitoring can correct management, decision-making plans, program or project that is being developed. People with credit favored human development associations once they have received training of entrepreneurship, it should be monitored so that it can guide you in your investments that are very small...